Theological content of Christian religious studies curriculum in Nigeria pastoral theology in secondary schools - Odia, Cyril Aigbadon (Oxford Bern Berlin Bruxelles New York Wien Peter Lang, 2020)
"Pastoral Theology is taught in secondary schools through the Christian Religious Studies (CRS) syllabus. The primary focus of this book is to present the theological content in the curriculum of CRS. It presents the actual content designed by educationists using the Nigerian model. This model has been discovered to be basically Christological in its approach. It is highly influenced by the historical influence of early Christian missionaries dating back to the 1500s and later structured after the English and Irish model before independence of many African countries. It shows why the teaching of CRS has stood the test of time within the various stages of the development of the secondary school syllabus. It proposes an African Theology of Education (ATE). It is linked with social Justice, public ethics and is closely connected with studying the Holy Bible"--
Includes bibliographical references and index
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Christian Education -- Nigeria; Religious Education -- Nigeria; Pastoral Theology -- Nigeria -- Study and teaching; Education (Christian theology); Theology -- Africa